GaN-nanopillar-based light-emitting diodes directly grown on multi-crystalline Si substrates - Yuichi Sato; Shingo Taniguchi; Sora Saito; Houyao Xue; Tsubasa Saito (AIP Advances, 2021)
For the first time, light-emitting diodes based on gallium nitride nanopillar crystals were prepared directly on a multi-crystalline silicon substrate, which is widely utilized in low-cost solar cells. Several double-hetero-p–n-junction structures were fabricated, and bright light emission was obtained from the diodes. In addition, white-light emission was observed in another diode. The multi-crystalline Si substrate can be added to a candidate substrate to realize practical, novel, large-area light-emitting devices.